2018
DOI: 10.1242/jeb.188649
|View full text |Cite
|
Sign up to set email alerts
|

Changes of gene expression but not cytosine methylation are associated with male parental care reflecting behavioural state, social context, and individual flexibility

Abstract: Behaviour is often a front line response to changing environments. Recent studies show behavioural changes are associated with changes of gene expression; however, these studies have primarily focused on discrete behavioural states. We build on these studies by addressing additional contexts that produce qualitatively similar behavioural changes. We measured levels of gene expression and cytosine methylation, which is hypothesized to regulate the transcriptional architecture of behavioural transitions, within … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 74 publications
3
22
0
Order By: Relevance
“…So while the initial response to the removal of care involves differential methylation in stress-related pathways, evolved differential methylation is enriched in processes associated with growth and brain development though this was not always associated with gene expression at the developmental point at which we measured it. DNA methylation in insects, including the burying beetle, appears to be stable across the lifespan (Cunningham et al, 2019; Yagound et al, 2020). This raises the possibility that DNA methylation may be a product of ancestral transcriptional states.…”
Section: Discussionmentioning
confidence: 99%
“…So while the initial response to the removal of care involves differential methylation in stress-related pathways, evolved differential methylation is enriched in processes associated with growth and brain development though this was not always associated with gene expression at the developmental point at which we measured it. DNA methylation in insects, including the burying beetle, appears to be stable across the lifespan (Cunningham et al, 2019; Yagound et al, 2020). This raises the possibility that DNA methylation may be a product of ancestral transcriptional states.…”
Section: Discussionmentioning
confidence: 99%
“…Mean and standard deviation of parenting was 11.67 ± 8.33 observations of feeding for the low group and 72.42 ± 2.18 observations of feeding for the high group, indicating substantial quantitative behavioral differences (Benowitz et al 2016b). We analyzed head tissue, which contains both brain and fat body, following previous studies that identified differential expression of genes associated with parenting in females (Parker et al 2015;Cunningham et al 2014Cunningham et al , 2016Cunningham et al , 2019Roy-Zokan et al 2015;Benowitz et al 2017a,b). We performed phenolchloroform extractions using Qiagen RNeasy Lipid Kits (Qiagen, Venlo, Netherlands) and synthesized cDNA using qScript (Quantabio, Beverly, MA) reverse transcriptase (Parker et al 2015;Roy-Zokan et al 2015).…”
Section: Methodsmentioning
confidence: 99%
“…Reflecting this, an RNA-seq study comparing non-parenting and parenting individuals identified broad transcriptional differences (> 700 genes) between the two states (Parker et al 2015). Transcriptional differences have also been defined for responses to social context and for plasticity in male parenting (Cunningham et al 2019). Thus, we have a clear phenotype with well characterized DE associations.…”
Section: Introductionmentioning
confidence: 95%
“…They found ~550, ~100, and ~20 genes associated with these variables, respectively, showing the greatest influence is from behavior. Biological function of these genes was associated with metabolism (Cunningham et al, 2019).…”
Section: Experimental Work Investigating Parental Care -Transcriptomesmentioning
confidence: 99%